2016
DOI: 10.1111/pde.12887
|View full text |Cite
|
Sign up to set email alerts
|

Koebner's Phenomenon in Childhood Henoch‐Schönlein Purpura: A Report of Two Cases

Abstract: Koebner's phenomenon occurs rarely in connection with Henoch-Schönlein purpura (HSP). We report two children with HSP who developed Koebner's phenomenon on the second day after the onset of rash. The first was an 11-year-old girl with rheumatic heart disease who presented with abdominal pain for 1 month and subsequently developed rash and nephritis. The second patient was a 7-year-old girl who presented with rash and polyarthritis. To the best of our knowledge, Koebner's phenomenon in childhood HSP has not bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
(10 reference statements)
0
5
1
Order By: Relevance
“…To date, fewer than 10 cases of nonblanching, palpable skin lesions with a linear pattern have been reported in both children and adults with Henoch-Schönlein syndrome. [2][3][4][5][6][7][8] The incongruity between what might be expected from the available literature and our experience is related to the fact that, for patients with Henoch-Schönlein syndrome, the physical skin examination focuses mainly on the distinctive palpable rash, which does not blanch with pressure and symmetrically affects the buttocks, legs, and feet. Unsurprisingly, therefore, it was not difficult for us to find images in the literature depicting the characteristic rash of Henoch-Schönlein purpura, [10][11][12] which was associated with evident linear lesions, although they were not specifically described as such in the image legends.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…To date, fewer than 10 cases of nonblanching, palpable skin lesions with a linear pattern have been reported in both children and adults with Henoch-Schönlein syndrome. [2][3][4][5][6][7][8] The incongruity between what might be expected from the available literature and our experience is related to the fact that, for patients with Henoch-Schönlein syndrome, the physical skin examination focuses mainly on the distinctive palpable rash, which does not blanch with pressure and symmetrically affects the buttocks, legs, and feet. Unsurprisingly, therefore, it was not difficult for us to find images in the literature depicting the characteristic rash of Henoch-Schönlein purpura, [10][11][12] which was associated with evident linear lesions, although they were not specifically described as such in the image legends.…”
Section: Discussioncontrasting
confidence: 57%
“…This tendency, often termed Köbnerization , is common in psoriasis, lichen planus, vitiligo, and many bullous dermatoses . Very rarely, such lesions have also been documented in patients with Henoch-Schönlein syndrome, an immunoglobulin A–dominant leukocytoclastic small vessel vasculitis . This report presents our prospective experience with linear nonblanching skin lesions in children with this vasculitis syndrome.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Further research is warranted to establish the role of COVID-19 behind the causation (if any). 6,7,8,9 Our case of post-Covid cutaneous small-vessel vasculitis with features of Koebnerization highlights the fact that COVID-19 may be associated with cutaneous manifestations even after recovery.…”
Section: I Scl a I M Ermentioning
confidence: 71%
“…6 A comprehensive literature review of reports published in the English language revealed a total of nine reports on KP in LCV. 2,613 Seven of the nine articles were reported in adults, while the remaining two articles were reported in the pediatric population. The majority of reports (seven articles) have been published on KP specifically in HSP, with the remaining two articles reporting KP in cases of medication-induced LCV.…”
Section: Discussionmentioning
confidence: 99%